(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Environmental pollutionis one of the biggest problems that the world faces today. It is an issue thattroubles us economically, physically and everyday of our lives. Thecontamination of the environment is also being linked to some of the diseasesthat are around currently. Yet, most people do not know about this problem.This shows that environmental pollution is becoming an increasingly worseproblem that needs to be taken care of as soon as possible, not only for thegood of the environment but also for the people that live in it. Many factorsare present for why environmental pollution has become such a large issue inthe world. However, if the people of the world were to address the issue, itwould definitely help both the environment and its people. There are manyactivities that can be done by both the common citizen to the governments ofthe world, which could severally improve the world’s environmental problem. Onthe other hand, if the current way the world’s environmental problem is beinghandled continues, catastrophic consequences can follow for the futurepopulation.